Model E-Business Untuk Klaster Industri Kerajinan Gerabah - Tutik Khotimah; - Darsin (Conference In Business, Accounting, And Management (CBAM), 2012)
Pottery industrys in sub-district Mayong regency Jepara are potentially industrial clusters. Pottery industrys to be pottery industry clusters are expected to eventually be able to manage the pottery industry to develop their potential, to compete with other pottery industry from other areas and potentially for export. In addition, the pottery industry clusters will be expected to assist the industry in meeting the needs of raw materials, labors, supporting materials, capitals, etc., also help the industry in distributing products to consumers directly like any distributor, and minimize competition between the fellow industry that maintained continuity of pottery industrys in sub-district Mayong regency Jepara. To sustain the pottery industrys, the development of e-business model is the right choice, responding to the issue of green business. The model will be expected to help the pottery industry clusters, both for internal activities (related to the production process) would also external activities (relating to consumer).Keywords: green business, e-business, industrial clusters, pottery industrys